Roles of linear and circular polarization properties and effect of wavelength choice on differentiation between ex vivo normal and cancerous gastric samples - Wang, Wenfeng (2014)
Multispectral Mueller matrix imaging was performed over a spectral range from 470 to 632 nm on 4-μm unstained gastric tissue sections. A complete set of polarization parameters was derived. The combination of linear depolarization and linear retardance yields the highest accuracy in sample classification. When the depolarization of linearly polarized light due to scattering is independent of the orientation angle of the incident linear polarization vector, the derivation of linear polarization properties will require only 3×3 Mueller matrix, which would significantly reduce the complexity of the polarimetry imaging system. When additional parameters are needed to complement the two linear polarization parameters, retardance, circular depolarization, and depolarization can be included in classification in the order of preference. However, these additional parameters would require the measurement of 4×4 Mueller matrix. In addition, it appears that wavelength is not a critical factor in terms of classification accuracy for thin tissue sections in this study.